Warung hierarki used civic educational learning for increase the participation of learning: experimental study - Indriyani, Dina; Rohimah, Ucu (Panicgogy International Journal, 2024)
The aim of this study is to examine the impact of using the Warung Hierarchy learning model on students' learning participation in the Citizenship Education (PPKn) learning process. Student participation is considered a key factor influencing their learning outcomes, and it is crucial for teachers to encourage active involvement in learning activities, as good participation can lead to optimal results. The researcher focuses on using an innovative learning model to enhance student participation. The experimental method was used, with the researcher testing the effect of the Warung Hierarchy model on improving learning participation. The study was conducted with students from a vocational school as the sample to evaluate the effectiveness of this model during PPKn lessons. The results indicate that implementing the Warung Hierarchy learning model can increase students' participation, which suggests that this model is effective in encouraging students to engage more actively in the learning process, ultimately positively influencing their learning outcomes.